Attitudes and preferences of visitors of Krka National Park, Croatia - Telbisz, Tamás; Šulc, Ivan; Mari, László; Radeljak KaufmannPetra (Hungarian Geographical Bulletin, 2022)
The primary function of national parks (NPs) is nature conservation, but for the majority of them, tourism also plays an important role. Tourism generates significant incomes, but the benefits are often unequally distributed in space, as are the disadvantages. The karst regions are generally less developed terrains in terms of traditional livelihoods, but due to their special morphology, tourism offers great opportunities. Nonetheless, mass tourism can also pose increased environmental risks. In this article, we examine the above questions on the example of Krka NP, especially from the perspective of tourists, as we conducted a questionnaire survey with visitors. The results confirmed that there is a high degree of spatial inequality both in the awareness of attractions and the distribution of tourist accommodation. This fact has already been recognised by the management of the NP, and serious steps have already been taken to reduce inequality, but their impact is not yet significant enough. Based on the survey, tourism in Krka NP is determined by same-day visits. Tourists who come here primarily consider waterfalls, lakes and rivers to be the most important values of the landscape, while cultural values are considered less significant and even less known. Local products are virtually unknown in the NP palette, so this could be a direction for development. Another point that could be developed is the awareness of visitors in the field of karstification. As the survey was conducted during COVID period, its impact on tourism was also briefly examined. This impact was manifested in the fact that the proportion of retirees and tourist buses was very small, whereas the majority of visitors (90%) arrived in the NP as independent travellers. For one third of foreigners, COVID played a role in choosing Croatia as a destination. As for domestic tourists, two thirds chose to find a destination in Croatia because of COVID.